Problems in Pronouncing the English Sounds Faced by the Students of SMPN 2 Halong, Banjar - Anis Komariah (Journal of English Language and Pedagogy, 2019)
This study entitled â€œProblems in Pronouncing The English Sounds Faced By The Students Of SMPN 2 Halong, Banjarâ€ is intended to find out the problems in pronouncing the English sounds faced by the students of SMPN 2 Halong, Banjar.This research uses qualitative method with contrastive analysis. The data were taken from the recorded studentsâ€™ voice. The researcher used recording, transcribing and analyzing technique. The researcher analyzed the data: 1. comparing English sounds and studentsâ€™ pronunciation, 2. finding out the consonant, vowel and diphthong mispronounced by the students, 3. finding out studentsâ€™ difficulties in pronouncing the English sounds, 4. finding out the studentsâ€™ problems in pronouncing English sounds, 5. drawing a conclusion. The Subjects of this research are Banjar students of ninth grade at SMPN 2 Halong.It is found out that the students had problems in pronouncing the English sounds of consonant (/t/, /Î¸/, /Êƒ/, /-t/, /f, /Ê’ /, /-d/), vowel (/É’/, /e/, /oÊŠ/) and diphthong( /eÉª/, /oÊŠ/, /É™ r /). The sounds /Î¸/ are pronounced as [t], /Êƒ/ is as [s], /É’ / as [u], /oÊŠ/ as [aw], /Ê’/ as [s], while /t/, /eÉª /, /-t/, /-d/ and /É™r/ are pronounced they are written. The error can be caused by the absence of the sound in their mother tongue.Â